A comparative study of geophysical measurements to characterise the local site condition of Bengkulu City, Indonesia - Lindung Zalbuin Mase; Samsul Bahri; Aliawan Saputra (International Association of Lowland Technology, 2020)
Bengkulu City is one of the vulnerable areas to undergo earthquakes in Indonesia. Two major earthquakes happened in 2000 and 2007 had appeared the issue that the site condition played the important role in determining the seismic effect in Bengkulu City. However, the detail understanding of local site condition including the parameter to measure it, is still not fully achieved. This paper presents a comparative study of geophysical measurement to characterise local site condition in Bengkulu City. The geophysical surveys using Multichannel Analysis of Surface Wave (MASW) and Ambient Noise of Microtremor methods are performed to several sites in Bengkulu City. Furthermore, the inversion analysis to generate shear wave velocity (Vs) is performed. The comparisons to site class and time-averaged shear wave velocity for first 30 m depth (Vs30) are also compared. The results show that MASW results tend to be more conservative than Microtremor results. However, both measurements show the similar tendency for site class condition. This study also proposed the empirical models in estimating Vs30 and seismic vulnerability (Kg) indices for Bengkulu City. Those models are reliable in engineering practice application in Bengkulu City.